“That wasn't really a place to worry about diabetes”: Housing access and diabetes self-management among low-income adults - Keene, Danya E.; Guo, Monica; Murillo, Sascha (Social science & medicine (1982), 2018)
Lack of affordable housing access represents a significant and growing problem for low-income households in the United States and these housing challenges may present barriers to the management of chronic diseases such as type 2 diabetes. In this qualitative study, we examined how both housing challenges and housing resources shaped diabetes self-management behaviors. We conducted semi-structured interviews with 40 low-income residents of one US city, New Haven, Connecticut, who had a diagnosis of type 2 diabetes and either resided in or qualified for subsidized housing. We purposively constructed our sample to include a range of housing experiences (subsidized, unsubsidized, homeless) and treatment regimes. We analyzed the data using grounded theory techniques of inductive coding and memo writing. Our findings suggest multiple ways that housing access can affect diabetes self-management with implications for blood glucose levels and future complications. Specifically, we describe the ways that housing access affected participants’ ability to: 1) prioritize their diabetes care, 2) establish and maintain diabetes routines, and 3) afford diabetes-related expenses. Together, our findings show how housing challenges increased the cost of adherence to diabetes management regimes such that inadequately housed individuals had to both invest and sacrifice more for the same outcomes. Our findings suggest that improved affordable housing access may represent an opportunity to improve outcomes and reduce socioeconomic disparities among those living with type 2 diabetes. •Housing access affects the prioritization of diabetes self-management.•Housing access affects the routinization of diabetes behaviors.•High housing costs compete with diabetes related expenses to affect self-management.•Improved affordable housing access may reduce disparities in diabetes outcomes.